Chemical Constituents of Dorstenia convexa (Moraceae) - Martial Poumale Poumale, Herve; Amadou, Dawe; Shiono, Yoshihito; Deccaux Wabo Fotso Kapche, Gilbert; Tchaleu Ngadjui, Bonaventure (Asian Journal of Chemistry, 2010)
Triterpenoids, sterols and coumarins were isolated from the leaves of Dorstenia convexa. Betulonic acid (2), platanic acid (3), betulinic acid (4), 3,20-dioxo-30-norlupan-28-oic acid (5), lupenone (11) and 29-norlupan-3,20-dione (12) are reported from Dorstenia genus for the first time. Some isolated compounds were evaluated for their antimicrobial activity. Compounds 5 and 12 as well as the crude CHCl3/MeOH (1:1) extract exhibited significant antimicrobial activity at 40 μg/mL.